2022
DOI: 10.3233/jad-220297
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological and Clinical Correlates of Lewy Body Disease Survival by Race and Ethnicity in the National Alzheimer’s Coordinating Center

Abstract: Background: Survival and associated clinical and pathological characteristics in Lewy body disease (LBD)-related dementias are understudied. Available studies focus primarily on white non-Hispanic samples. Objective: We investigated demographic, clinical, and pathological correlates of survival by race and ethnicity in an autopsy-confirmed cohort of LBD cases. Methods: Using National Alzheimer’s Coordinating Center data, we selected participants who self-identified as Black, Hispanic, or white who had neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This finding confirms our result that patients with LBD autopsy have a lower diagnosis accuracy compared with other groups even at later dementia stages. The results from Kurasz et al (2022) demonstrate that Black/African American participants were less likely to receive LBD as the clinical primary diagnosis despite having a higher frequency of diffuse LBD pathology than their White and Hispanic counterparts. Another study ( Chatterjee et al, 2021 ) noted that autopsy-confirmed AD+LBD had a premortem syndrome with higher prevalence of memory issues and less classical LBD symptoms compared to pure LBD pathology.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding confirms our result that patients with LBD autopsy have a lower diagnosis accuracy compared with other groups even at later dementia stages. The results from Kurasz et al (2022) demonstrate that Black/African American participants were less likely to receive LBD as the clinical primary diagnosis despite having a higher frequency of diffuse LBD pathology than their White and Hispanic counterparts. Another study ( Chatterjee et al, 2021 ) noted that autopsy-confirmed AD+LBD had a premortem syndrome with higher prevalence of memory issues and less classical LBD symptoms compared to pure LBD pathology.…”
Section: Discussionmentioning
confidence: 90%
“…Yet, AD+LBD presented with more parkinsonism, visual hallucinations, RBD and cognitive fluctuations than pure AD. Many of these studies ( Surendranathan et al, 2020 ; Chatterjee et al, 2021 ; Kurasz et al, 2022 ) confirm that autonomic dysfunction (urinary incontinence, orthostatic hypotension) and repeated falls could be a significant diagnostic clue for LBD pathology (pure or mixed).…”
Section: Discussionmentioning
confidence: 95%
“…It is also possible that clinicians are predisposed to give AD dementia diagnoses to Black individuals based on the research showing high prevalence in this population. These hypotheses are supported by NACC research showing that 88% of Black participants with Lewy body pathology (65% diffuse, 35% transitional) were assigned a primary etiologic cause of AD clinically, with only 5% assigned a secondary diagnosis of suspected Lewy body disease despite 70% having sufficient Lewy body pathology to predict an intermediate-high likelihood of a clinical DLB presentation [ 5 ]. Unrecognized Lewy body disease could also potentially help explain lower proportions of amyloid PET positivity among Black adults with MCI or dementia [ 21 ].…”
Section: Dementia and Racementioning
confidence: 91%
“…In NACC, there were no differences in the frequency of hallucinations or delusions between racial-ethnic groups in individuals clinically diagnosed with cognitive impairment due to Lewy body disease [ 22 ]. In individuals with Lewy body disease pathology, there were also no statistically significant differences in the frequency of visual hallucinations reported between racial-ethnic groups [ 5 ]. These findings are in contrast to a NACC study using all-cause dementia, where the odds of experiencing hallucinations and delusions were over double among Black participants with dementia (versus White) and other neuropsychiatric symptoms were also more common in Black participants [ 23 ].…”
Section: The Intersection Of Race and Core Features Of Dlbmentioning
confidence: 99%
See 1 more Smart Citation